Anatomy of Lamina in the Subaxial Cervical Spine With the Special Reference to Translaminar Screws: CT and Cadaveric Analysis With Screw Trajectory Simulation. Issue 5 (June 2017) - Cho, Woojin; Le, Jason T.; Shimer, Adam L.; Werner, Brian C.; Glaser, John A.; Shen, Francis H.
Abstract : Study Design: A cadaveric study. Summary of Background Data: Translaminar screws were initially developed for C2 fixation. Since then, their usage has expanded to include the subaxial cervical spine, and thoracic and lumbar spine. To the best of our knowledge, special anatomy for inserting translaminar screws in the subaxial cervical spine has not been studied. Objective: To report the special anatomy for inserting translaminar screws in the subaxial cervical spine. Methods: A total of 18 cadaveric spines were harvested from C3 to C7 and 1 mm computed tomography (CT) scans and 3D reconstructions were obtained. Bilateral translaminar screw entry points and trajectories were simulated at each level from C3 to C7 utilizing Kodak Carestream/Pacs Ver 10.2. Constructs were selected to achieve maximal bony purchase with 1 screw, designated the "primary screw." The contralateral screw, designated the "secondary screw, " was selected to achieve the optimal allowable diameter possible while avoiding a simulated cortical breach, which was not always necessarily the "best purchase" diameter. Initial screw diameters selected were 3.5 mm; however, in the event that a narrower portion was encountered, then a 3.0 mm diameter screw was utilized instead. The crossing area of both screws were calculated geometrically. Maximal thickness of the lamina was considered in determining the diameter of screws. Whenever possible, 3.5 mm screws were selected in both lamina (3.5/3.5 mm); however, if a 3.5 mm screw was utilized as the primary screw, but the permissible range ( P ) for the secondary screw was <3.5 mm, then a hybrid construct was utilized (3.5/3.0 mm). In cases where P was <3 mm, then both screws were studied at 3 mm (3.0/3.0 mm). Screw diameters that optimized trajectory and bony purchase, while remaining within the permissible range, were analyzed, tabulated, and recorded. On CT, along the trajectory of the screws, the image was cut and measured in terms of screw length, the narrowest portion of the lamina, vertical angle, and horizontal angle in both primary and secondary screws. On the individually separated cervical spine segments in cadavers (11 of 18), we performed caliper measurements on the same portions that were measured on CT. It could not be exactly the same portions, however, due to the 3-dimensional characteristics of the specimens. Results: For C3, only 1 specimen allowed 2 screws (3/3 mm), while the remaining specimens permitted a unilateral primary screw (3.5 or 3 mm) only. For C4, 37% of specimens allowed 2 screws (3.5/3 mm or 3/3 mm), but the rest allowed only a unilateral primary screw (3.5 or 3 mm). For C5, 58% allowed 2 screws (3.5/3.5, 3.5/3, or 3/3 mm). For C6, 89% of specimen allowed 2 screws (3.5/3.5, 3.5/3, or 3/3 mm). For C7, all levels allowed 2 screws (3.5/3.5, 3.5/3, 4/4, 4/3, 4.5/3, 4.5/3.5, or 4/3.5 mm). On CT, the average lengths of the 1- and 2-degree screws were 26.14 and 24.01 mm, respectively. The average vertical and horizontal angles were 22.26 and 40.66 degrees for the 1-degree screw, and 3.45 and 45.59 degrees for the 2-degree screw. On cadavers, the average lengths of the 1- and the 2-degree screws were 22.58 and 23.44 mm, respectively. The average vertical and horizontal angles were 23.67 and 54.44 degrees for the 1-degree screw, and 2.28 and 54.89 degrees for the 2-degree screw. Conclusions: This is a report of the anatomy of the lamina in the subaxial cervical spine with the special reference to translaminar screws. It was analyzed with CT and cadaveric spines along with simulated screw trajectories. For the 1-degree translaminar screw, the entry point is the distance of the diameter of desired screw superior to the inferior margin of lamina-spinous process junction. The trajectory should be targeted toward the most superomedial corner of lateral mass. For the 2-degree translaminar screw, the entry point is the distance of the diameter of desired screw below the superior margin of lamina-spinous process junction, and the target is the most superolateral corner of lateral mass, which is typically horizontal. Further studies are needed to assess the feasibility of translaminar screw insertion in the actual subaxial cervical spine.